Dinamika Mepeduluhi Masyarakat Wawonii di Desa Langara Iwawo Kecamatan Wawonii Barat Kabupaten Konawe - Syamsumarlin . (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2013)
ABSTRACT The objective in this study is to discover the dynamics or cooperation development of Wawonii communities in the West Wawonii District that called mepeduluhi. Mepeduluhi is a mutual aid system or performing work in rotation according to the cultural conventions that became a farmer coalition model. This research was conducted by using ethnographic methods, with qualitative descriptive analysis. Method of data collection was done by observation and in-depth interviews. The results showed that mepeduluhi has changed on Wawonii community in the Langara Iwawo village. This could be seen in economic activity, which almost all of them have worked with the wage system. Societies have understood that any economic activity should be reward. This phenomenon was caused by the inclusion PMPN Mandiri that helped villagers. Key words: dynamics, mepeduluhi, farmers’ cooperation